Reform of Anglo-American Complicity Law: Conduct, Connectivity and Comparative Solutions. (December 2022) - Reed, Alan
The challenge presented by extant Anglo-American complicity law is that it intractably homogenises different participatory modalities across a broad landscape of culpability, and ultimately the controller/instigatory actor may be treated alike with the ethereal shadow marionette. It is essential to effect change, not only as a concern of appropriate legal substantive reformulation, but also to avoid capricious practical unfairness. It should not be reforms predicated on the illusory distillation of causality requirements, between assistance and encouragement provided by the accessory and direct commission of harm(s), but rather on an imputed-normative-proportionality standardisation, reviewable via evidentiary perspectives in terms of actual intercessory conduct. A critique of alternative legal system approaches to complicitous behaviour, notably the Germanic Criminal Code, provides further significant insights towards the adaptation of a new accessorial liability framework. This broadened template promulgates a synchronous and complementary original review of withdrawal precepts. A redemptive change of heart aligned with appropriate reductive criminal depredation may exculpate via reverse conduct prophylaxis. Only an individual actor who has manifestly interceded in criminal harm(s), adjudged by the jurors as moral arbiters within prescribed gradations of culpability, as addressed herein, should rank imputably in equiparated blameworthiness with the principal offender. If this equiparation is lacking, or if the criminal wrongdoing is characterised as a wholly independent action by another party, then alternative forms of potential secondary party liability must be sought – a de novo facilitation offence as propounded subsequently, and consideration of reverse burden of proof.